Sinomenine Provides Neuroprotection in Model of Traumatic Brain Injury via the Nrf2–ARE Pathway - Yang, Youqing; Wang, Handong; Li, Liwen; Li, Xiang; Wang, Qiang; Ding, Hui; Wang, Xiaoliang; Ye, Zhennan; Wu, Lingyun; Zhang, Xiangsheng; Zhou, Mengliang; Pan, Hao (Frontiers in Neuroscience, 2016)
The neuroprotective effect of sinomenine (SIN) has been demonstrated in several brain injury models. However, its role and molecular mechanism in traumatic brain injury (TBI) remain unknown. In this study, we investigated the neuroprotective effects of SIN in the weight-drop model of TBI in male ICR mice. Mice were randomly divided into the sham and TBI groups, SIN (10 mg/kg, 30 mg/kg and 50 mg/kg, administered intraperitoneally) or equal volume of vehicle was given at 30 min after TBI. SIN (30 mg/kg) significantly attenuated secondary brain injury, measured by neurological deficit, brain water content, and neuronal apoptosis. Furthermore, SIN significantly increased the expression of Bcl-2 and decreased that of cleaved caspase-3, indicating that SIN is anti-apoptotic. This was confirmed by the observation that SIN-treated animals had fewer apoptotic neurons. Cortical malondialdehyde content, glutathione peroxidase activity and superoxide dismutase activity were restored in the group that received SIN. Furthermore, western blot and immunofluorescence experiments showed that SIN enhanced the translocation of nuclear factor erythroid 2-related factor 2 (Nrf2) to the nucleus. SIN administration also significantly upregulated the expression of the downstream factors heme oxygenase 1 and NAD(P)H:quinone oxidoreductase 1 at pre- and posttranscriptional levels. Together, these data demonstrate that SIN exerts a neuroprotective effect in a model of TBI, possibly by activating the Nrf2–antioxidant response element pathway.